2008
DOI: 10.1021/es801372q
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Optimization of Heterogeneous Photo-Fenton Process with Response Surface Methodology and Artificial Neural Networks

Abstract: In this study, estimation capacities of response surface methodology (RSM) and artificial neural network (ANN) in a heterogeneous photo-Fenton process were investigated. The zeolite Fe-ZSM5 was used as heterogeneous catalyst of the process for degradation of C.I. Acid Red 14 azo dye. The efficiency of the process was studied as a function of four independent variables, concentration of the catalyst, molar ratio of initial concentration of H2O2 to that of the dye (H value), initial concentration of the dye and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
120
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(120 citation statements)
references
References 26 publications
0
120
0
Order By: Relevance
“…The application of these statistical techniques in experiments has the advantages of requiring fewer resources (time, numbers of duplication, and amount of experimentation), but can also reduce process variability [23]. RSM is a collection of statistical and mathematical techniques useful for developing, improving, and optimizing processes [24]. These techniques relate a response variable to predictors that have multiple levels.…”
Section: Experimental Designmentioning
confidence: 99%
“…The application of these statistical techniques in experiments has the advantages of requiring fewer resources (time, numbers of duplication, and amount of experimentation), but can also reduce process variability [23]. RSM is a collection of statistical and mathematical techniques useful for developing, improving, and optimizing processes [24]. These techniques relate a response variable to predictors that have multiple levels.…”
Section: Experimental Designmentioning
confidence: 99%
“…This algorithm is belonging to the gradient descent backpropagation. The details of the algorithm have been reported elsewhere [14]. It was reported in literature that the quick propagation learning algorithm can be adopted for the training of all the ANN models [15].…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…Kasiri et al modeled and optimized the heterogeneous photo-Fenton process using both response surface methodology (RSM) and ANN [57], with the experimental measured H2O2 concentration, catalyst concentration, initial pH, and initial dye concentration as the inputs of the models. They found that for a catalyst design process, ANN is as powerful as RSM.…”
Section: Prediction Of Reaction Descriptorsmentioning
confidence: 99%